63.0k views
0 votes
What is the answer. 5 + (-11) - (-11).

User BSavaliya
by
5.2k points

2 Answers

2 votes
0=5+(-11)-(-11)

We simplify the equation to the form, which is simple to understand
0=5+(-11)-(-11)

Remove unnecessary parentheses
0=+5-11-(-11+)

Remove unnecessary parentheses
0=5-11+11

We move all terms containing to the left and all other terms to the right.
0=+5-11+11-0

We simplify left and right side of the equation.
0=+5

0=5

The left and right sides are not equal, therefore there is no solution. This equation is invalid.
User Wbruntra
by
5.4k points
3 votes

Answer:

Lemme see I odnt know

Explanation:

User Bandula Dharmadasa
by
4.8k points